Seguridad y salud ocupacional en la productividad laboral del personal de obra del Grupo Inmobiliario Altitud S.A.C. de Ilo, 2023 - Ormeño Collao, Felix Yian Piero (2024)
This research analyzes occupational health and safety and its relationship with the productivity of the personnel of the Villa Primavera Urban Enabling Work of the Company Grupo Inmobiliario Altitud S.A.C. of the city of Ilo, in the year 2023. Objective: Determine how occupational health and safety influences the work productivity of the construction staff of the Company Grupo Inmobiliario Altitud S.A.C. of Ilo, year 2023. Method: Basic type, with an explanatory level and non-experimental design, the study sample consisted of 217 workers, to whom the survey and questionnaire instrument were applied as a technique. Results and conclusions: It will be determined that occupational health and safety influences the work productivity of the construction staff of the Company Grupo Inmobiliario Altitud S.A.C. of Ilo, year 2023. This link, demonstrated by a significance value of less than 0.05 in the Rho-Spearman test, reinforces the theory that effective health and safety practices not only protect workers, but also improve their efficiency. and performance. The positive perception of these practices among employees suggests that investment in a safe and healthy work environment based on compliance with adequate conditions, environmental conditions, a positive work environment, compliance with work requirements, and adequate work organization . of prevention, are crucial factors to increase labor and institutional productivity.